2020
DOI: 10.1111/mec.15497
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of environmental variability influence coral‐associated bacterial and algal communities on the Mesoamerican Barrier Reef

Abstract: A coral's capacity to alter its microbial symbionts may enhance its fitness in the face of climate change. Recent work predicts exposure to high environmental variability may increase coral resilience and adaptability to future climate conditions. However, how this heightened environmental variability impacts coral‐associated microbial communities remains largely unexplored. Here, we examined the bacterial and algal symbionts associated with two coral species of the genus Siderastrea with distinct life history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…While coral microbiomes are generally comprised of species-specific communities [11,12], environmental perturbations like nutrient or temperature fluxes can induce compositional shifts that vary both spatially [13] and temporally [14][15][16][17]. It has been proposed that coral species that maintain stable microbiomes may be more tolerant to environmental stressors [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…While coral microbiomes are generally comprised of species-specific communities [11,12], environmental perturbations like nutrient or temperature fluxes can induce compositional shifts that vary both spatially [13] and temporally [14][15][16][17]. It has been proposed that coral species that maintain stable microbiomes may be more tolerant to environmental stressors [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Gene categorization was performed based on Kyoto Encyclopedia of Genes and Genomes Orthology (KO) designations. Differential expression analysis was performed through DeSeq2 and as described previously (66). Briefly, a contingency table was generated by comparing average transcript per sample abundances between treatments using a one-way analysis of variance (ANOVA) corrected for multiple comparisons using the false discovery rate (FDR).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Indeed, previous work has observed that greater coral tissue biomass follows increased symbiont density and chlorophyll a content in several Caribbean reef-building coral species [27], highlighting the intrinsic relationship with algal symbionts to support the coral host's energy budget. Further, previous work has reported the influence of algal symbiont and microbiome communities as mechanisms of improving coral holobiont physiology under environmental stress [28][29][30][31][32]. Overall, it is clear that maintaining healthy symbioses within the coral holobiont is critical for the physiological health of the coral host.…”
Section: Introductionmentioning
confidence: 96%